2002
DOI: 10.1128/jcm.40.10.3602-3605.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candida glabrata by a 30-Second Trehalase Test

Abstract: Rapid (30-s) trehalase tests done with material from colonies of 482 yeasts suspended in a drop of trehalose solution on a commercially supplied glucose test strip were positive for 225 (99.1%) of 227 Candida glabrata isolates grown on either of two differential media, Candida ID medium or CandiSelect medium. The test was positive for only 3 (1.2%) and 12 (4.7%) of 255 isolates of other medically important yeast species grown on the same two media, respectively. A rapid maltase test done with a subset of 255 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Discrepancies between VITEK 2, ITS-FLP, and the reference method were analyzed by repeated testing of the discrepant method and by additional tests (pigmentation of colonies on CHROMagar Candida [Chromagar Microbiologie, Paris, France] and morphology on Cornmeal-Tween 80 agar [OX-OID, Hampshire, United Kingdom]) (11). Rapid trehalose and maltose tests were used as additional tests for the identification of C. glabrata (5,6).…”
mentioning
confidence: 99%
“…Discrepancies between VITEK 2, ITS-FLP, and the reference method were analyzed by repeated testing of the discrepant method and by additional tests (pigmentation of colonies on CHROMagar Candida [Chromagar Microbiologie, Paris, France] and morphology on Cornmeal-Tween 80 agar [OX-OID, Hampshire, United Kingdom]) (11). Rapid trehalose and maltose tests were used as additional tests for the identification of C. glabrata (5,6).…”
mentioning
confidence: 99%
“…Uninterpretable results had previously been explained by the carryover of glucose-containing agar in the yeast suspension (7). However, laboratories C and F, both using Sabouraud-chloramphenicol agar with 4% dextrose, obtained rates of uninterpretable results of 0.9 and 22.4%, respectively.…”
mentioning
confidence: 90%
“…It is based on the ability of C. glabrata to hydrolyze trehalose and includes both a maltose test and a control test to improve the specificity of the test as previously recommended (7,15). In a preliminary study with 330 stock isolates, GLABRATA RTT reliably identified C. glabrata subcultured on three commonly used chromogenic media: Candida ID, CandiSelect, and CHROMagar Candida (8).…”
mentioning
confidence: 99%
“…A variety of tests have been developed for the rapid characterization of yeast isolates. These include the rapid assimilation of trehalose by Candida glabrata, the detection of rapid urease production or the detection of phenoloxidase by the caffeic acid disk test for Cryptococcus neoformans, and the germ tube test or the detection of a colonial fringe on primary isolation media for the identification of C. albicans (2,(4)(5)(6)20). A subculture onto specialized CHROMagar is another means of differentiating yeasts (19,22).…”
mentioning
confidence: 99%